Respuestas
Respuesta dada por:
0
Binomio al cuadrado.
![(a + b)^{2} = a^{2} + 2ab + b^{2} (a + b)^{2} = a^{2} + 2ab + b^{2}](https://tex.z-dn.net/?f=%28a+%2B+b%29%5E%7B2%7D+%3D+a%5E%7B2%7D+%2B+2ab+%2B+b%5E%7B2%7D)
![=================================== ===================================](https://tex.z-dn.net/?f=%3D%3D%3D%3D%3D%3D%3D%3D%3D%3D%3D%3D%3D%3D%3D%3D%3D%3D%3D%3D%3D%3D%3D%3D%3D%3D%3D%3D%3D%3D%3D%3D%3D%3D%3D)
![(x + 7)^{2} = 49 (x + 7)^{2} = 49](https://tex.z-dn.net/?f=%28x+%2B+7%29%5E%7B2%7D+%3D+49)
![x^{2} + 2(x)(7) + 7^{2} = 49 x^{2} + 2(x)(7) + 7^{2} = 49](https://tex.z-dn.net/?f=+x%5E%7B2%7D+%2B+2%28x%29%287%29+%2B++7%5E%7B2%7D+%3D+49)
![x^{2} + 14x + 49 = 49 x^{2} + 14x + 49 = 49](https://tex.z-dn.net/?f=+x%5E%7B2%7D+%2B+14x+%2B+49+%3D+49+)
![x^{2} + 14x + 49 - 49 = 0 x^{2} + 14x + 49 - 49 = 0](https://tex.z-dn.net/?f=+x%5E%7B2%7D+%2B+14x+%2B+49+-+49+%3D+0+)
![x^{2} + 14x = 0 x^{2} + 14x = 0](https://tex.z-dn.net/?f=+x%5E%7B2%7D+%2B+14x+%3D+0+)
Sacas factor común x.
![x(x + 14) = 0 x(x + 14) = 0](https://tex.z-dn.net/?f=x%28x+%2B+14%29+%3D+0)
Tenemos una solución.
![x + 14 = 0 x + 14 = 0](https://tex.z-dn.net/?f=x+%2B+14+%3D+0)
![x = - 14 x = - 14](https://tex.z-dn.net/?f=x+%3D+-+14)
Solución:
(- 14).
Sacas factor común x.
Tenemos una solución.
Solución:
(- 14).
Preguntas similares
hace 7 años
hace 7 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años